Nomads of the Mediterranean: trade and contact in the Bronze and Iron Ages : studies in honor of Michal Artzy - Leṿinzon-Gilboʻa, Ayelet; Yasʿur-Landau, Assaf (Culture and history of the ancient Near East, 2020)
"Three millennia of cross-Mediterranean bonds are revealed by the 18 expert summaries in this book-from the dawn of the Bronze Age to the budding of Hellenization. An international team of acclaimed specialists in their fields-archaeologists, historians, geomorphologists, and metallurgists-shed light on a plethora of aspects associated with travelling this age-old sea and its periphery: environmental factors; the formation of harbors; gateways; commodities; the crucial role of metals; cultural impact; and the way to interpret the agents such as Canaanites, "Sea Peoples," Phoenicians, and pirates. The book will engage any student of the Old World in the 3000 years before the Common Era"--